2017
DOI: 10.1021/acsami.7b02775
|View full text |Cite
|
Sign up to set email alerts
|

Functional Silver Nanocomposites as Broad-Spectrum Antimicrobial and Biofilm-Disrupting Agents

Abstract: Biofilms' tolerance has become a serious clinical concern due to their formidable resistance to conventional antibiotics and prevalent virulence. Therefore, there is an urgent need to develop alternative antimicrobial agents to eradicate biofilms but avoid using antibiotics. Herein, we successfully developed polymer functional silver nanocomposites by reduction of silver nitrate in the presence of a biocompatible carbohydrate polymer and a membrane-disrupting cationic polymer. The nanocomposites presented effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 70 publications
2
50
0
Order By: Relevance
“…Although the antibacterial nanoparticles are considered as promising candidates for addressing AMR, multiple cycles of treatment below lethal concentration also led to gradual increases in MIC of AgNPs, which exacerbates our concerns about whether biofilm exhibits tolerance and resistance to it. In this study, the results showed that AgNPs possessed the strong dose‐dependent anti‐biofilm capacities, which conformed to previous work . It is worth noting that P aeruginosa biofilm became more resistant to AgNPs.…”
Section: Discussionsupporting
confidence: 91%
“…Although the antibacterial nanoparticles are considered as promising candidates for addressing AMR, multiple cycles of treatment below lethal concentration also led to gradual increases in MIC of AgNPs, which exacerbates our concerns about whether biofilm exhibits tolerance and resistance to it. In this study, the results showed that AgNPs possessed the strong dose‐dependent anti‐biofilm capacities, which conformed to previous work . It is worth noting that P aeruginosa biofilm became more resistant to AgNPs.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, increase of fungal inhibition depends on NPs concentration as well as particle size, as the smaller particle size prompts extensive membrane permeability and cell destruction . Smaller particle size has large surface area that could be firmly absorbed on the surface of the microbial cells so as to dismantle the membrane, which leads to effluence of intracellular components, consequently killing the microorganisms …”
Section: Resultsmentioning
confidence: 99%
“…[12] Taken the biocompatibility into consideration, the phase transfer agent should be removed from GOHCM before biological applications, because of the cytotoxicity of cationic surfactants via destroying the electric balance between the inner and outer of the cell membrane. [32] After tested with a series of organic solvents, ethanol was found to be an efficient and safe extractant. As shown in Figure S8 in the Supporting Information, the hierarchical structures consisting of microscale honeycomb patterns and nanoscale textures were well maintained because of the strong affinity between adjacent graphene oxide sheets.…”
Section: Preparation Of Self-assembled Go Honeycomb Microarraymentioning
confidence: 99%